Effect of Bioculture on Drinking Water on Feed Consumption and Average Daily Gain (ADG) of Fat Tailed Sheep - Nurazizah, Rahmahwati; Setyaningrum, Agustinah; Sumarmono, Juni (Bulletin of Applied Animal Research, 2023)
Body weight is the main productivity parameter in sheep as a beef cattle. Bioculture is a prebiotic that is made from spices and fruits which are extracted and dissolved with mollases and probiotic starter. Bioculture is believed to be able to increase the performance and productivity of sheep. This research was conducted to examine the effect of giving bioculture to drinking water on feed consumption and average daily gain for sheep. Twelve months old male fat tail sheep as many as 18 were reared for 6 weeks. The research method used was experimental with a Cross Random Design (CRD), consisting of 3 treatments with 6 replications of 6 samples. The treatment consisted of P0: 60% odot grass + 40% concentrate (control); P1: control + 0.5% bioculture; and P2: control + 1% bioculture. The data were analyzed using Kruskal Wallis test. The results showed that the addition of bioculture in drinking water had a significant effect on consumption P<0.05. The higher the level of bioculture, the higher the feed consumption. On the other hand, giving bioculture had no significant effect on average daily gain of sheep P>0.05. This study shows that bioculture can increase feed consumption, but has not been able to increase the average daily gain of fat-tailed sheep.